2008
DOI: 10.1111/j.1743-6109.2008.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peyronie's Disease on Sexual and Psychosocial Functioning: Qualitative Findings in Patients and Controls

Abstract: Introduction There are no validated scales for assessing the psychosocial impact of Peyronie's disease (PD), which affects approximately 5–10% of men over age 50. Aim To develop a psychometrically valid outcome measure for assessing psychosocial and sexual consequences of PD. To conduct a qualitative study of men with PD and age-matched controls, and design a new patient-reported outcome measure of PD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
166
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(177 citation statements)
references
References 18 publications
5
166
0
6
Order By: Relevance
“…Although curvature is the hallmark symptom of disease, shortening can be the most psychologically devastating, occurring in 70% of patients and ranging from 1 to 10 cm. 2,3 Determining whether there is a family history of PD or other fibrotic disorders such as Dupuytren's is also useful as it does appear to occur more frequently among males in the same family and through generations.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although curvature is the hallmark symptom of disease, shortening can be the most psychologically devastating, occurring in 70% of patients and ranging from 1 to 10 cm. 2,3 Determining whether there is a family history of PD or other fibrotic disorders such as Dupuytren's is also useful as it does appear to occur more frequently among males in the same family and through generations.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…Although diminished rigidity may be associated with several underlying medical conditions such as diabetes, smoking and peripheral vascular disease, it may also be psychogenic in nature given the devastating psychological effects that PD has on the affected individual. 2,13 Questions regarding sexual dysfunction should include ejaculation, orgasm, and change in sensation.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…2,8 Although pain typically resolves over time, 1 penile curvature or deformity persists and may impact patients' psychological health, relationships with their sexual partners, and emotional well-being. 9,10 For example, a singlecenter, cross-sectional study demonstrated that more than half of patients with PD experienced relationship problems because of the condition, and 81% reported emotional problems. 9 Furthermore, an observational study of 92 men with PD demonstrated that almost half (48%) indicated that they were depressed and that the depression had not resolved over time.…”
mentioning
confidence: 99%
“…Factors underlying this connection remain unknown, 13 but both conditions have been associated with increased age, 2,14-16 comorbid disorders (eg, diabetes, 2,8,16 cardiovascular events, 17,18 radical prostatectomy 19,20 ), psychological symptoms, [9][10][11]15,21,22 and altered blood flow. 13 In addition, ED has been associated with depression, 22 which, similar to PD, may influence a patient's assessment of physical and psychological functioning.…”
mentioning
confidence: 99%